PRILAKU SELF CARE DENGAN KUALITAS HIDUP - Ida Suryawati; Yudi Akbar; Cut Sri Wahyuni (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2022)
Hypertension is one of the leading causes of death in the world. The prevalence of hypertension is increasing because of the ineffectiveness of hypertension self-care. Correct and well-managed self-care management is needed to maintain blood pressure stability and improve quality of life. This study aims to determine the relationship between self-care and the quality of life of hypertensive patients at the Nisam Antara Health Center in North Aceh. This is an analytical research project with a cross-sectional study approach. The population in this study was 920 people with hypertension. Sampling using stratified random sampling with a sample of 90 people using the Slovin formula The results of statistical tests using the Chi-square test showed that the p-value was 0.000 0.05, meaning that there was a significant relationship between self-care and the quality of life of hypertensive patients at the Nisam Antara Health Center in North Aceh. It is recommended to the respondents that they be able to maintain and increase their knowledge by looking for more references about self-care and regularly participating in several activities about hypertension self-care to improve their quality of life.